Equine Hoof Canker: Cell Proliferation and Morphology. (July 2017) - Apprich, V.; Licka, T.; Zipfl, N.; Tichy, A.; Gabriel, C.
Hoof canker is described as progressive pododermatitis of the equine hoof with absent epidermal cornification and extensive proliferation of the dermal papillary body; however, in-depth research on the type of proliferative activity has not yet been reported. The aim of the present study was to determine cell-specific proliferation patterns together with morphological analysis of hoof canker tissue. Tissues removed during surgery from 19 horses presented for treatment of canker were compared with similar postmortem tissues of healthy hooves of 10 horses. Morphological alterations visible in light microscopy were assessed semiquantitatively and graded for severity. Proliferative activity was evaluated by means of anti-PCNA (proliferative cell nuclear antigen) and anti-Ki67 immunohistochemistry. Histologically, canker tissue showed 5 major morphological alterations–the presence of lacunae, vacuoles, giant cells, hemorrhage, and inflammation–not seen in control tissue. Also, there was a notable koilocytotic appearance of keratinocytes in canker tissue. Immunohistochemistry revealed increased levels of PCNA protein expression in keratinocytes and fibroblasts of canker tissue compared with control tissue. In control tissue, keratinocytes showed higher levels of Ki67 compared with canker tissue, while the dermal fibroblasts of both groups showed similar levels of Ki67, indicating similar proliferative activity of less than 3% of total dermal fibroblasts. These results demonstrate that, in contrast to previous reports, there is no evidence for increased proliferative activity of the dermal papillary body associated with hoof canker. Increased levels of PCNA protein expression and morphological alterations indicate that dysregulation of keratinocyte differentiation constitutes a key event in equine hoof canker development.